The Prevalence of xerostomia occurrence after doing radiation therapy in patients with head and neck cancer - Barunawaty Yunus (Journal of Dentomaxillofacial Science, 2017)
Xerostomia is one side effect of radiation therapy that most commonly affects head and neck. This situation is a symptom and not a disease which is generally associated with reduced saliva. For patients this situation is not pleasant and for dentist, this symptom is considered as a challenging case. This research intended to know the prevalence of xerostomia after radiation therapy in cancer patients with head and neck area. The subjects of this study were patients with head and neck area cancer who underwent radiotherapy treatment at Hasanuddin University teaching hospital, subjects were then taken saliva before and after given a total dose of 20 Gy and a total dose of 40 Gy. The analysis of the data processed by the computer program and the Wilcoxon test significance level is accepted when p<0.05. The mean bulk saliva before radiotherapy was higher than average rainfall saliva after radiotherapy total dose of 20 Gy and 40 Gy. Radiotherapy of the head and neck area total dose of 20 Gy and 40 Gy may affect rainfall saliva so that patients feel the symptoms of xerostomia.